2015
DOI: 10.47210/bjohns.2015.v23i2.43
|View full text |Cite
|
Sign up to set email alerts
|

Rhinosporidiosis: Various Presentations and Different Sites

Abstract: IntroductionRhinosporidiosis commonly affects nasal mucosa but may have varied presentations depending upon the site of involvement. Materials and Methods119 patients of rhinosporidiosis, attending the two medical colleges of West Bengal over a period of two years were reviewed. ResultsGranulomatous lesion in the nose and nasopharynx was the commonest presentation. The most common symptoms were nasal obstruction, bleeding from the nose and nasal discharge. The less commonly involved sites were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…4 Most of the patients presented with unilateral nasal obstruction followed by nasal bleeding. 4 Similar results found in studies conducted by Guru et al, and Bandyopadhyay et al 5,6 The most common site involved is nasal mucosa followed by nasopharynx, oropharynx, tracheobronchial tree, esophagus, conjunctiva and ears. 7 Cutaneous and visceral involvement occurs following disseminated disease.…”
Section: Discussionsupporting
confidence: 76%
“…4 Most of the patients presented with unilateral nasal obstruction followed by nasal bleeding. 4 Similar results found in studies conducted by Guru et al, and Bandyopadhyay et al 5,6 The most common site involved is nasal mucosa followed by nasopharynx, oropharynx, tracheobronchial tree, esophagus, conjunctiva and ears. 7 Cutaneous and visceral involvement occurs following disseminated disease.…”
Section: Discussionsupporting
confidence: 76%
“…Bandyopadhyay et al showed similar results in their study. 14 Guru and Pradhan found most of their patients presented with epistaxis, followed by nasal discharge, nasal obstruction, sneezing and anosmia. 8 Guru and Pradhan in their study found a greater number of cases with nasal involvement than those with extra-nasal involvement.…”
Section: Discussionmentioning
confidence: 96%
“…Although the typical look of rhinosporidiosis is usually sufficient to arrive at a diagnosis, delayed presentation, extra nasal presentation or involvement of multiple anatomically unrelated sites make the diagnosis difficult. 14 All cases of nasal and nasopharyngeal rhinosporidiosis were treated by wide endoscopic excision and cauterization of the base by diathermy. The case of disseminated rhinosporidiosis presented with a pedunculated rhinosporidial mass arising from the posterolateral wall of the trachea which was treated with the help of a special endotracheal tube designed by the anesthetist, and using a 6 mm rigid bronchoscope, the pedunculated mass was removed.…”
Section: Discussionmentioning
confidence: 99%
“…Although the typical look of rhinosporidiosis, a fleshy mulberry-like mass with dotted sporangia, is usually sufficient to arrive at a clinical diagnosis, delayed presentation and extranasal involvement of multiple anatomically unrelated sites sometimes make the diagnosis difficult. [ 14 ] The clinical presence of typical nasal cavity lesion, with multiple lesions in the other parts of respiratory tract or elsewhere in the body is enough to make a correct diagnosis.…”
Section: Discussionmentioning
confidence: 99%